Neonatal pain management practices in Somali region of Ethiopia: insights from neonatal intensive care unit providers - Abebe, Dawit; Orcho, Afework; Chane, Jemberu; Mesfin, Sinetibeb; Seifu, Wubareg (Frontiers in Pediatrics, 2024)
Background: Neonates admitted to Neonatal Intensive Care Units experience an average of 8 to 17 moderate to severe painful procedures per day. Because neonates lack the cognitive capacity to express their pain's location or severity, they are very dependent on the healthcare provider to recognize, assess, and manage their pain. The health and development of newborns are negatively impacted by persistent or untreated pain experienced early in life. So, the study on neonatal pain management practice and associated factors in healthcare is critical to tackling workforce problems, enhancing neonatal care, and lowering the long-term health impacts of neonates. From January 1 to 30, 2023, a facility-based cross-sectional study design was used at six public hospitals in the Somali region of Ethiopia. 336 healthcare providers enrolled using a simple random sample technique. A self-administered, structured questionnaire was utilized to collect the data. The analyses used bivariate and multivariate logistic regression. To find the association between the outcome and predictor factors, the odd ratio and the 95% CI were computed. The study reveals that 35.4% [95%CI 30.4%-40.5%] of respondents reported that they were found to have good neonatal pain management practices. Ever having training in neonatal pain assessment and management [AOR=2.26 (95% CI 1.259,4.07)], availability of pain assessment tools [AOR=3.05(95% CI 1.249,7.469)], and having a favorable attitude toward neonatal pain management practice [AOR= 3.71(95% CI 1.525,9.035)] are factors significant association with neonatal pain management practice. Based on the study's findings, there is a low level of neonatal pain management practice among healthcare providers in the Somali region. The study emphasizes the significance of having access to pain assessment tools as well as the requirement for healthcare professionals to get training on neonatal pain assessment and management.